Different Spatial and Temporal Roles of Monocytes and Monocyte-Derived Cells in the Pathogenesis of an Imiquimod Induced Lupus Model - Nomura, Atsushi; Mizuno, Miho; Noto, Daisuke; Aoyama, Aki; Kuga, Taiga; Murayama, Goh; Chiba, Asako; Miyake, Sachiko (Frontiers in Immunology, 2022)
Mounting evidence indicates the importance of aberrant Toll-like receptor 7 (TLR7) signaling in the pathogenesis of systemic lupus erythematosus (SLE). However, the mechanism of disease progression remains unclear. An imiquimod (IMQ)-induced lupus model was used to analyze the lupus mechanism related to the aberrant TLR7 signals. C57BL/6 mice and NZB/NZW mice were treated with topical IMQ, and peripheral blood, draining lymph nodes, and kidneys were analyzed focusing on monocytes and monocyte-related cells. Monocytes expressed intermediate to high levels of TLR7, and the long-term application of IMQ increased Ly6Clo monocytes in the peripheral blood and Ly6Clo monocyte-like cells in the lymph nodes and kidneys, whereas Ly6Chi monocyte-like cell numbers were increased in lymph nodes. Ly6Clo monocyte-like cells in the kidneys of IMQ-induced lupus mice were supplied by bone marrow-derived cells as demonstrated using a bone marrow chimera. Ly6Clo monocytes obtained from IMQ-induced lupus mice had upregulated adhesion molecule-related genes, and after adoptive transfer, they showed greater infiltration into the kidneys compared with controls. RNA-seq and post hoc PCR analyses revealed Ly6Clo monocyte-like cells in the kidneys of IMQ-induced lupus mice had upregulated macrophage-related genes compared with peripheral blood Ly6Clo monocytes and downregulated genes compared with kidney macrophages (MF). Ly6Clo monocyte-like cells in the kidneys upregulated Il6 and chemoattracting genes including Ccl5 and Cxcl13. The higher expression of Il6 in Ly6Clo monocyte-like cells compared with MF suggested these cells were more inflammatory than MF. However, MF in IMQ-induced lupus mice were characterized by their high expression of Cxcl13. Genes of proinflammatory cytokines in Ly6Chi and Ly6Clo monocytes were upregulated by stimulation with IMQ but only Ly6Chi monocytes upregulated IFN-α genes upon stimulation with 2′3′-cyclic-GMP-AMP, an agonist of stimulator of interferon genes. Ly6Chi and Ly6Clo monocytes in IMQ-induced lupus mice had different features. Ly6Chi monocytes responded in the lymph nodes of locally stimulated sites and had a higher expression of IFN-α upon stimulation, whereas Ly6Clo monocytes were induced slowly and tended to infiltrate into the kidneys. Infiltrated monocytes in the kidneys likely followed a trajectory through inflammatory monocyte-like cells to MF, which were then involved in the development of nephritis.